2000
DOI: 10.2307/2667070
|View full text |Cite
|
Sign up to set email alerts
|

The Collective Construction of Work Group Moods

Abstract: We thank Elaine Hatfield for providing us with several pre-publication materials that facilitated this research. Special thanks also go to Rod Kramer and three anonymous reviewers who provided substantial and constructive feedback and to Linda Johanson for her insightful editorial assistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
538
2
15

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 557 publications
(567 citation statements)
references
References 58 publications
12
538
2
15
Order By: Relevance
“…Qualitative and quantitative research methods could examine the types of group norms that emerge over time across cultures as a function of the "felt accountability" attributes discussed previously. For example, following the methodology of Bartel and Saavedra (2000) who examined the collective construction of group moods, one could use observational techniques to code the verbal and nonverbal elements of group interactions that encourage flexibility versus control across cultures. Quantitative methodologies for longitudinal data analysis (e.g., latent growth modeling; Chan, 2003) will also be useful for examining the emergence of group norms regarding flexibility and control across time as a function of a cultural group's profile on felt accountability characteristics.…”
Section: Bottom-up Processes Reinforcing Tightness In Organizationsmentioning
confidence: 99%
“…Qualitative and quantitative research methods could examine the types of group norms that emerge over time across cultures as a function of the "felt accountability" attributes discussed previously. For example, following the methodology of Bartel and Saavedra (2000) who examined the collective construction of group moods, one could use observational techniques to code the verbal and nonverbal elements of group interactions that encourage flexibility versus control across cultures. Quantitative methodologies for longitudinal data analysis (e.g., latent growth modeling; Chan, 2003) will also be useful for examining the emergence of group norms regarding flexibility and control across time as a function of a cultural group's profile on felt accountability characteristics.…”
Section: Bottom-up Processes Reinforcing Tightness In Organizationsmentioning
confidence: 99%
“…In a study on the degree to which verbal and nonverbal cues can be observed by others, Bartel and Saavedra (2000) developed a taxonomy of verbal expressions, facial expressions, and body postures that were indicative of self-reported moods. During several observations of work group members, observers were able to use this taxonomy to accurately identify participants' moods.…”
Section: Interactionmentioning
confidence: 99%
“…Within teams, affectivity has been an increasingly powerful lens for studying emotion. Groups frequently converge in the tendencies of individuals to experience particular emotional states and this convergence generally has beneficial consequences for teams (e.g., Barsade Gibson, 1998;Barsade, Ward, Turner, & Sonnenfeld, 2000;Bartel & Saavedra, 2000;George, 1990;Kelly & Barsade, 2001;Totterdell, 2000). A limitation of the existing body of studies is the sampling exclusively from Western cultural groups, so the applicability to other cultures remains untested.…”
Section: Emotional Experience In Groups and Teamsmentioning
confidence: 99%
“…If, as discussed above, individual sensitivity to others' emotional states is the building block for team-level phenomena such as group mood and emotional contagion (e.g., Bartel & Saavedra, 2000;Barsade, 2002;George, 1990), then decreased sensitivity to the emotions of members of other cultural groups serves to weaken these phenomena. Examining the convergence and spread of emotional states across team members in terms of each step in the process model, first members are likely to have greater initial diversity in their emotional states.…”
Section: Cultural Diversity As Emotional Containment and Amplificationmentioning
confidence: 99%
See 1 more Smart Citation